Die heuristiese potensiaal van narratiwiteit vir sosiaal relevante Sistematiese Teologie: Jürgen Moltmann se oorlogservarings as voorbeeldstudie - Van Wyk, Tanya ca. 20./21. Jh. (HTS teologiese studies, 2013)
The heuristic potential of narrativity for socially relevant Systematic Theology: The world war experiences of Jürgen Moltmann as case study. The article argues that an argumentative discourse should be complemented by a narrative discursive mode to express the connectedness between experience and the social context in which people’s life history is embedded. The article’s point of departure is Jean-Baptisté Metz’s notion of the ‘practical, liberating character of narrative’. An example of such a narrative systematic discourse is the approach of Michael Weinrich in which he replaces logos (ratio) with mythosis. The latter includes narratio, whilst logos does not. The life history of Jürgen Moltmann as contextual theologian serves as case study to demonstrate the heuristic potential of narrativity for contextual systematic theology. Moltmann’s autobiography The Broad Place functions as the frame of reference for such a narrative approach to systematic theology.